Strengthening Digital Literacy In Building Critical Thinking - Salahuddin, Salahuddin; Hasanah, Dewi; Hasanah, Neneng; Asmawati, Asmawati; Ekafitrianda, J. M.; Saputra, Edi; Neni, Neni; Jessica, Melia (Lembaga Dongan Dosen, 2025)
Community service activities were carried out by the Islamic Religious Education Study Program team of UIN Sultan Thaha Saifuddin Jambi at IAI Al-Mujaddid Sabak Tanjung Jabung Timur with the aim of strengthening students' critical thinking skills in the era of the Industrial Revolution 4.0. This training was attended by 30 students and 15 lecturers from various educational backgrounds. In this activity, students were given an explanation and understanding of the use of technology for learning purposes, Exploring the creative side through multimedia, this activity is to support a more innovative and interactive learning process, allowing students to deliver material in a more interesting and easy-to-understand way. In addition, this activity is also a forum for expressing creative ideas conceptually and practically. Students are invited to discuss and share experiences on effective ways to integrate digital technology in learning, in order to improve students' critical and creative thinking skills. Therefore, this training aims to increase awareness, knowledge, and skills in optimizing the learning process. The results of this socialization showed that participants were very enthusiastic and actively participated, despite challenges related to access to adequate devices. This digital literacy activity is expected to improve critical thinking skills among students and can continue to develop, along with technological advances in this modern era